Pengaruh Sistem Reservasi Ruang Diskusi Open Library Berbasis Website Terhadap Produktivitas Civitas Akademik Telkom University - Mohamad Rafki Nazar; Agung Kurniawan; Fani Irdina; Shabrina Novita Maulani; Shely Sukmana Putri (Peneliti.net, 2023)
This study is motivated by the rapid development of science and technology, one of which is in the field of information technology. As technology develops, companies and government agencies use computer systems as a tool to make work easier. Telkom University Open Library as one of Telkom University's academic supports is also inseparable from the use of technology, one of which is by using a website-based discussion room reservation system. This study aims to determine the effect of the website-based Open Library discussion room reservation system on the productivity of the Telkom University academic community. Based on the results of the discussion, it was found that this website-based discussion room reservation system makes it easy for the Telkom University academic community in data collection and reporting as well as in making it easier for students to order Open Library discussion rooms.